Analysis of sports management students’ opinions on project-based learning - Ahmet Şahin (Türk Spor ve Egzersiz Dergisi, 2018)
The purpose of this study is to analyze Sports Management Students’ Opinions on Project-Based Learning. A great majority of the sports management students who participated in the study do sports regularly and only a little portion of 3.3 % stated that they do not do sports at all. In order to determine the attitudes of students towards the method of Project-Based Learning, an attitude scale -originally called Project-Based Learning Attitude Scale (PBLAS), which consisted of a total of 26 items (13 positive and 13 negative) was prepared after receiving the expert opinion of Sezgin in 2008. The ratio of female sports management students who read books is higher that the ratio of male students. On the other hand, the frequency of visiting entertainment venues is higher for male students compared to female students. When the average scores of the answers given to the Project-Based Learning scale are observed, it can be concluded that the students who participated in the study were eager to make use of the benefits of project-based learning, however because they were also affected from negative cases, they were often undecided. When the opinions of the project-based learning study participants are analyzed according to gender, it can be claimed that for the 4 items that were available in the scale, male students had more positive opinions compared to female students. It can be also seen that more female students expressed positive opinions for item first.